PENGARUH KETELADANAN KEPALA SEKOLAH, MOTIVASI KERJA DAN SARANA PRASARANA TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA NEGERI SE KECAMATAN BANTUL TAHUN PELAJARAN 2012/2013 (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
The Influence of School Role model, Work Motivation, and Infrastructure on the Performance of State Junior High Schools Teachers in the Regency of Bantul. This study is purposed to describe the influence of school Role model, work motivation, and infrastructure on the performance of state junior high school teachers in the Regency of Bantul on academic year of 2012/2013. This research is a quantitative correlational approach. The data wos taken from the population, i.e. from the state junior high schools teachers in the Regency of Bantul. The sampling used a proportionate random sampling. The techniques of data collection use questionnaire instruments. The analysis techniques used multiple regression techniques with three predictors. The simultaneous hypothesis testing uses F-test or ANOVA were are followed by partial hypothesis tests, i.e. with t-test. The data were tested using analysis of test requirements, i.e. the normality test, linearity, and multicollinearity test with a significance level of 5%. Based on the research results, it can be concluded that: (1) there is a positive and significant simultaneous influence of school Role model, work motivation, and infrastructure on the performance of state junior high school teachers in the Regency of Bantul; (2) there is a negative and significant partial influence of school Role model on the performance of state junior high school teachers in the Regency of Bantul; (3) there is a negative and significant partial influence of working motivation on the performance of state junior high school teachers in the Regency of Bantul; and (4) there is a positive and not significant partial influence of infrastructure on the performance of state junior high school teachers in the Regency of Bantul. The simultaneous effective contribution is 81,8%. The partial effective contribution of (1) the school Role model on the performance of state junior high school teachers in the Regency of Bantul is 31,3%; (2) the work motivation on the performance of state junior high school teachers in the Regency of Bantul is 14.2%; and (3) the infrastructure on the performance of state junior high school teachers in the Regency of Bantul is 30,6%.